Diversity and species composition of ants at coffee agroforestry systems in East Java, Indonesia: Effect of habitat condition and landscape composition - FAIZ NASHIRUDDIN MUHAMMAD; AKHMAD RIZALI; BAMBANG TRI RAHARDJO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Muhammad FN, Rizali A, Rahardjo BT. 2022. Diversity and species composition of ants at coffee agroforestry systems in East Java, Indonesia: Effect of habitat condition and landscape composition. Biodiversitas 23: 3313-3321. Habitat condition and landscape composition are the main factors that shape biodiversity in agroecosystems. However, information on the effect of habitat conditions and landscape composition on biodiversity in agroforestry systems is lacking. Agroforestry systems possess habitats that are characterized by a high diversity of vegetation, that can support biodiversity both on the field or landscape scale. This research aimed to study the diversity and species composition of ants in coffee (Coffea spp.) agroforestry systems, and to investigate the effects of habitat conditions and landscape composition on ant communities. Field research was conducted in twelve coffee agroforestry systems in East Java, Indonesia. Ants were sampled with the fogging method for canopy ants and pitfall traps for ground-dwelling ants in 40 m x 30 m plots. In each location, habitat conditions aspects (such as cultural technique and tree age) were identified by interviews with farmers and vegetation observation. Meanwhile, landscape composition was characterized by ground checking and mapping the land-use type within a 500 m radius from plot centers. This research recorded 35 species and 4,622 individuals of ants from all coffee plantations. Dolichoderus thoracicus was the most dominant canopy ant, while Pheidole sp.2 was the most dominant ground-dwelling ant in all plantations. Based on the GLM analysis, different responses were found between canopy and ground-dwelling ants in relation to habitat conditions and landscape composition. Canopy and ground-dwelling ants were affected by habitat conditions (such as tree age and canopy cover). The species composition of ground-dwelling ants was also affected by habitat conditions. In conclusion, habitats in coffee plantations can affect ant communities with ground-dwelling ants being more sensitive than canopy ants. Meanwhile, landscape composition can affect the species richness of all ants and not affect each stratum (canopy and ground-dwelling ants).